2017
DOI: 10.18632/oncotarget.16823
|View full text |Cite
|
Sign up to set email alerts
|

Better cancer specific survival in young small cell lung cancer patients especially with AJCC stage III

Abstract: It has been reported that younger patients with non-small cell lung cancer (NSCLC) tend to have a better prognosis. Yet, few studies have focused on the clinicopathological characteristics and prognosis of young small cell lung cancer (SCLC), especially for patients with age < 50. In our study, we used Surveillance, Epidemiology, and End Results (SEER) population-based data and identified 16503 patients with SCLC including 711 patients aged < 50, 3338 patients aged 50–59, 5937 patients aged 60–69, 4649 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…Older age, aggressive stage of the tumor, large tumor sizes, lymph node invasion and distant metastasis were correlated with poor prognosis. Consistent with that for other tumors, younger patients had relatively better survival than older patients [ 13 ]. Age was an independent prognostic indicator in one study [ 12 ].…”
Section: Discussionsupporting
confidence: 79%
“…Older age, aggressive stage of the tumor, large tumor sizes, lymph node invasion and distant metastasis were correlated with poor prognosis. Consistent with that for other tumors, younger patients had relatively better survival than older patients [ 13 ]. Age was an independent prognostic indicator in one study [ 12 ].…”
Section: Discussionsupporting
confidence: 79%
“…Similar to other types of cancer, younger patients often had much better prognosis than older patients. 10 As for SmCC of the salivary gland, a previous study also found that age was a statistically significant prognostic factor with the 5-year survival rate of younger patients (<65 years) almost 6-fold (63.5% vs 11.5%) that in older patients (≥65 years). We also observe that marital status could affect prognosis in patients with SmCC of the salivary gland in univariate analysis and this is echoed in previous data on a strong positive correlation between marriage and prognosis of cancer patients that married status had a lower HR of tumor occurrence.…”
Section: Discussionmentioning
confidence: 93%
“…Studies on IIIa/IIIb NSCLC cases not receiving MWA showed a 5-year OS range between 5 and 25%, and a CSS range between 10 and 36% (10,2932). In the present report, the 5-year OS was 18.3%, while the 5-year CCS was 30.0%.…”
Section: Discussionmentioning
confidence: 99%